OSTEOPOROSIS HEALTH INFORMATION IN THE ELDERLY AT POSYANDU ANGGREK, NITIPURAN, SONOSEWU, BANTUL - Venny Diana (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
Osteoporosis is a bone disease characterized by decreased bone mass and deteriorating microstructural bone so that bones become brittle and increase the risk of fracture. Osteoporosis is one of the causes suffering and disability especially in the elderly, in the form of fractures, body defects, and complications that can cause death. Based on a preliminary study at the Posyandu Anggrek, from 45 elderly people who were present at that time, 20 of them said did not know about Osteoporosis, besides that cadres from the Elderly Posyandu Anggrek said that so far there had never been any counseling about Osteoporosis. The purpose of this counseling is to increase the knowledge of the elderly about Osteoporosis so that elderly know the current condition of bone health. The method used in this activity is counseling with videos, powerpoint and using leaflets. The elderly who attended this activity were 45 people consisting of 2 men and 43 women, with an age distribution of 10 people in the middle age category, 18 people in the elderly category and 17 people in the old category. After counseling about Osteoporosis, there was a discussion session for the elderly, as many as 29 people could answer the questions this was because some of the elderly were not active in activities and there was 1 elderly with a wheelchair condition so they were more passive. The conclusion of this activity is the level of knowledge of elderly at the Posyandu Anggrek at Sonosewu increased 64.4% from the previous 26.6%.